Fluoride removal from aqueous solution by electrocoagulation using aluminium electrodes: Isotherm and kinetic studies - Yazici Guvenc, Senem; Varank, Gamze; Demir, Ahmet (PAMUKKALE UNIV, 2018)
The main objective of the present study was the removal of fluoride from aqueous solution by electrocoagulation technique using aluminum electrodes. The effect of various parameters such as current density, time and initial fluoride concentration were studied to optimize the conditions. Experimental study showed that maximum removal efficiency (87.4%) was achieved at the conditions of current density 11 mA/cm(2), reaction time 30 min and initial fluoride concentration 10 mg/ L. Isotherm models (Langmuir and Freundlich) and kinetic models (pseudo-first order and pseudo-second order) were used to analyze the electrocoagulation mechanism and characterize the process parameters. Experimental data well fitted with Langmuir and Freundlich isotherm equations and results of the kinetic study indicated that pseudo-second order kinetic model give higher correlation coefficients for different conditions.
Keywords: Electrocoagulation; Fluoride removal; Isotherm and kinetic models; WASTE-WATER; DRINKING-WATER; ADSORPTION; 2-PARAMETER; SEPARATION; Engineering